The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1139/v96-081
|View full text |Cite
|
Sign up to set email alerts
|

Spectator catalysis in the cleavage of p-nitrophenyl acetate and p-nitrophenyl hexanoate by "hydroxypropyl-β-cyclodextrin"

Abstract: Aliphatic alcohols that form host-guest complexes with "hydroxypropyl-P-cyclodextrin" retard the cleavage of tnnitrophenyl acetate by hydroxypropyl-P-cyclodextrin in basic aqueous solution, due to competitive inhibition. By contrast, these same species do not inhibit the reaction of p-nitrophenyl acetate and p-nitrophenyl hexanoate to the same extent and, in some cases, the addition of alcohols serves to increase the rate of reaction. The observed reaction kinetics require the presence of a process that has on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…The values obtained for MB + and BNAH were 130 and 220 dm 3 mol -1 , respectively. These values were considerably smaller than those obtained for the formation of 1:1 complexes between MB + (BNAH) and β-CD in aqueous solution (values of 420 [19] and 460 dm 3 mol -1 [29] for MB + and 810 dm 3 mol -1 for BNAH [30] were reported).…”
Section: Effect Of β-Cd On the Hydride Transfer Reaction Between Bnahcontrasting
confidence: 63%
“…The values obtained for MB + and BNAH were 130 and 220 dm 3 mol -1 , respectively. These values were considerably smaller than those obtained for the formation of 1:1 complexes between MB + (BNAH) and β-CD in aqueous solution (values of 420 [19] and 460 dm 3 mol -1 [29] for MB + and 810 dm 3 mol -1 for BNAH [30] were reported).…”
Section: Effect Of β-Cd On the Hydride Transfer Reaction Between Bnahcontrasting
confidence: 63%
“…Since this earliest work, a number of esters have been examined that bind into the cyclodextrin cavity and then react with a cyclodextrin hydroxyl group. These include derivatives of adamantane , and of various other hydrophobic species, in some cases with enantioselectivity. ,, The structural selectivity of such hydrolyses has been used for the analysis of mixtures . Particularly interesting are some cases (e.g.…”
Section: Simple Cyclodextrinsmentioning
confidence: 99%
“…Cyclodextrins (CDs) form inclusion complexes with a wide variety of species in aqueous solution . As a result they have effects on the rates of organic reactions, ranging from complete inhibition through mild retardation to significant catalysis, depending on the reaction and the CD. These features have been observed for basic ester cleavage in the presence of CDs, which has been investigated by many groups, including ours. By contrast, the effect of CDs on the reactions of esters with nucleophiles besides hydroxide ion have received little attention. It was reported that nucleophilic attack of α-amino acid anions on p -nitrophenyl acetate (pNPA) can be catalyzed by CDs,9a but a later study in our laboratory showed that the catalytic effect is less than originally thought 9b…”
Section: Introductionmentioning
confidence: 99%